An Investigation of the Effect of Chitosan on Isothermal Crystallization, Thermal Decomposition, and Melt Index of Biodegradable Poly(L-lactic acid) - Yan-Hua Cai; Li-Sha Zhao (International Journal of Polymer Science)
Biodegradable chitosan (CS) was introduced into another biodegradable poly(L-lactic acid) (PLLA) to prepare the PLLA/CS composites, and the effect of CS on thermal behavior and melt index of PLLA was investigated using modern testing technologies including optical depolarizer, thermogravimetric analysis instrument, and melt index instrument. The relevant testing results showed that both crystallization temperature and CS concentration affected the isothermal crystallization behavior of PLLA. Compared to neat PLLA, the t1/2 of PLLA/5% CS decreased from 2991.54 s to the minimum value 208.76 s at 105°C. However, the t1/2 of PLLA/CS composites in high crystallization temperature zone was different from that in low crystallization temperature zone. The increase of CS concentration and heating rate made the thermal decomposition temperature of PLLA/CS composites shift to higher temperature. The melt index results indicated that 3% CS made the fluidity of PLLA become better.